High-flow nasal cannula versus Nasal continuous positive airway pressure among preterm babies with respiratory distress syndrome - Media Khalid Abduallah (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: HHFNC(humidified high-flow nasal cannula) and NCBAP(Nasal Continuous Positive Airway Pressure) are Known ventilator support widely used in pediatric intensive care unit with specific indications. Advantage and disadvantages of both we discussed in many literatures and both improved outcome of patients with proper setting and less side effects.Objectives: We aimed to evaluate the use of both procedures in very to moderate preterms with RDS and to study the predictors associated with their success/failure Materials and Methods : A cross-sectional study was conducted at Intensive Care Unit of Rapareen Teaching Hospital in Erbil during the period from January till December 2023, sixty-five preterm babies of 28-33 weeks with respiratory distress syndrome (RDS) were enrolled in this study. Results: The study included 65 patients with Mean gestational age of 30.62 ± 1.62 and median GA 31m, majority were aged 3 days and male mainly product of caesarian delivery. Significant association was evident between need for NCPAP upon HHFNC with female gender and lower birth weight. Pneumothorax was among serious complications noted highly among NCPAP patients compared to HHFNC. Conclusions: NCPAP more frequent among low birth weight and increase likelihood of pneumothorax in comparison to HHFNC. No one of procedures have advantage over other regarding length of stay at hospital or death rate.